TRANSFORMATIONS OF MANAGEMENT TECHNOLOGIES (MANIPULATION ASPECTS) - R. S. Yunusova (Russian Journal of Economics and Law)
Basing on the analysis of the works by thinkers and researchers, classical and behavioral concepts of management, as well as modern managerial paradigms, the author views the evolution of managerial technologies; defines the manipulative essence of managerial activity; reveals the peculiar features and consequences of implementing the manipulative technologies of management.